2021
DOI: 10.1177/09610006211063938
|View full text |Cite
|
Sign up to set email alerts
|

Computer self-efficacy, computer anxiety, cognitive skills, and use of electronic library resources by social science undergraduates in a tertiary university in Nigeria

Abstract: This study investigated the influence of computer self-efficacy, computer anxiety, and cognitive skills on the use of electronic library resources by social science undergraduates in a tertiary institution in Nigeria. Survey research design was adopted and stratified random sampling technique was used to select 869 sample size from a population of 1452 social science undergraduates across five departments. A total of 793 questionnaire was properly filled and collated which equals a response rate of 91.3% from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Other studies have shown that instructional methods that promote group discussion and metacognitive learning [25,27,28], which allow students to control their cognitive processes, can also reduce learning anxiety, and thereby improve students' interest in learning and overall achievement. Thus, a negative correlation has since been established between anxiety and students' achievement in science [29][30][31] through empirical studies. While several teaching methods with these characteristics have been experimented with and used over time by teachers to teach chemistry in our classrooms, poor attitude to learning and show of lack of interest indicates that the pervasiveness of anxiety still persists.…”
Section: Anxiety and Chemistry Learningmentioning
confidence: 99%
“…Other studies have shown that instructional methods that promote group discussion and metacognitive learning [25,27,28], which allow students to control their cognitive processes, can also reduce learning anxiety, and thereby improve students' interest in learning and overall achievement. Thus, a negative correlation has since been established between anxiety and students' achievement in science [29][30][31] through empirical studies. While several teaching methods with these characteristics have been experimented with and used over time by teachers to teach chemistry in our classrooms, poor attitude to learning and show of lack of interest indicates that the pervasiveness of anxiety still persists.…”
Section: Anxiety and Chemistry Learningmentioning
confidence: 99%
“…Technology (computer) has advanced in recent times and prints are giving way to the use of electronic library resources for information search and utilization especially in the academic environment, this rapid technological change has a great impact on and poses challenges to the education system most important individuals with computer anxiety (Agboola, Bamigboye & Owolabi, 2019). The effect computer anxiety has on a student is gross which in turn influence their electronic library use, and several factors that can influence computer anxiety among undergraduate students such as feelings of frustration, potential embarrassment, disappointment, fear of the unknown and experiencing a feeling of helplessness (Tuncer 2012;Popoola & Adedokun, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Understanding the prevalence and characteristics of these platforms is essential for assessing their suitability and effectiveness in supporting teaching and learning activities (Popoola & Adedokun, 2023;Quadri et al, 2014). Additionally, evaluating the usability and accessibility of existing web-hosted e-learning platforms provides valuable insights into the challenges and opportunities associated with their implementation (Yebowaah & Plockey, 2018;Linjawi & Alfadda, 2018).…”
Section: Introductionmentioning
confidence: 99%